2014
DOI: 10.1371/journal.pntd.0002873
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of the Risk of Dengue and the Entomological Indicators in Sumaré, State of São Paulo, Brazil

Abstract: Dengue fever is a major public health problem worldwide, caused by any of four virus (DENV-1, DENV-2, DENV-3 and DENV-4; Flaviviridae: Flavivirus), transmitted by Aedes aegypti mosquito. Reducing the levels of infestation by A. aegypti is one of the few current strategies to control dengue fever. Entomological indicators are used by dengue national control program to measure the infestation of A. aegypti, but little is known about predictive power of these indicators to measure dengue risk. In this spatial cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…Other studies conducted in Taiwan, Sri Lanka and Vietnam [13,14,29] have shown that larval indices may be closely related to the incidence of dengue epidemics and arboviruses. In Brazil, similar research was conducted in Rio de Janeiro, São Paulo and Maranhão [14,18,19].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies conducted in Taiwan, Sri Lanka and Vietnam [13,14,29] have shown that larval indices may be closely related to the incidence of dengue epidemics and arboviruses. In Brazil, similar research was conducted in Rio de Janeiro, São Paulo and Maranhão [14,18,19].…”
Section: Discussionmentioning
confidence: 96%
“…The presence or absence of dengue vectors is measured using three key indices: house index (HI: the percentage of houses infested with larvae and/or pupae); Breteau index (BI: the number of positive containers per 100 houses); container index (CI: the percentage of water-holding containers infested with larvae or pupae) [12,13]. These indices may facilitate understanding of the ecology of vectors in a given control area, but they also serve as useful measures for determining the success of intervention strategies [11,14].…”
mentioning
confidence: 99%
“…6 and 7. Past literature has discussed that mosquito indices could not comprehensively reflect the risk of dengue fever (Barbosa et al, 2014;Bowman, Runge-Ranzinger, & McCall, 2014;Sulaiman, Pawanchee, Arifin, & Wahab, 1996). Additionally, the incidence of dengue cases as a risk indicator could only reflect the risk of residence but not contain the exposure risk of daily lives, which may appear in different settings.…”
Section: Discussionmentioning
confidence: 99%
“…The response variable is the observed dengue cases, dm y , where denotes the district and denotes as month, m. Due to the high variability in the monthly dengue counts, the data set, was assumed to follow the negative binomial distribution to handle the presence of overdispersion. The final model could be arranged such as in (1). The final model was referred from the previous study by [18].…”
Section: Model Developmentmentioning
confidence: 99%
“…Many infectious diseases are known to be carried by mosquitoes such as chikungunya, dengue, malaria and yellow fever. Dengue as the critical infectious disease since 1986 and Brazil was the first country confirmed with the outbreaks [1]. In Malaysia, DIR has grown severely and now significantly become a major public health concern to authority.…”
Section: Introductionmentioning
confidence: 99%